Boswellia hesperia sp. nov. (Burseraceae) from Socotra - Thulin, Mats; Weber, Michael; Mubarak, Sami Ali Mohammed; Rzepecky, Alain (Nordic journal of botany, 2025)
The new species Boswellia hesperia Thulin, M.H.Weber and Rzepecky is described, illustrated and mapped. It is a dwarf tree, restricted to westernmost Socotra (Yemen), growing on limestone rocks, in which the usually prostrate stems tend to fill out holes and crevices. It differs from B. nana Hepper, another dwarf tree endemic to Socotra but restricted to the easternmost parts of the island, by having leaves densely pubescent with whitish hairs beneath and by its smaller flowers and fruits.